2005
DOI: 10.1002/masy.200550312
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Layered Silicate/Carbon Nanotube Nanocomposites: Morphological and Rheological Properties

Abstract: Morphological and rheological properties of new ternary nanocomposites based on ethylene vinyl acetate copolymers (EVA), commercial organo‐modified clays (organoclays) and purified multi‐walled carbon nanotubes (MWNTs), prepared via direct melt blending, have been evaluated. For sake of comparison, the corresponding binary compositions, i.e., EVA filled with either organoclays or MWNTs, have been investigated as well. While extensive exfoliation can be observed for binary EVA/clay nanocomposites, the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The morphological, mechanical and rheological properties of the samples have already been described [8]. Morphological characterization by TEM and AFM showed a rather limited extent of NTs dispersion in EVA, many agglomerations were still visible forming long bundles of NTs.…”
Section: Nanocomposite Preparationmentioning
confidence: 79%
See 2 more Smart Citations
“…The morphological, mechanical and rheological properties of the samples have already been described [8]. Morphological characterization by TEM and AFM showed a rather limited extent of NTs dispersion in EVA, many agglomerations were still visible forming long bundles of NTs.…”
Section: Nanocomposite Preparationmentioning
confidence: 79%
“…Morphological characterization by TEM and AFM [8] showed a rather limited extent of NTs dispersion in EVA, many agglomerations were still visible forming long bundles of NTs. The crushed MWNTs have a much shorter length and intermediate flexibility that provide a better nanotube dispersion.…”
Section: Influence Of the Mwnts Morphology (3 Wt% Of Mwnts)mentioning
confidence: 99%
See 1 more Smart Citation
“…The MWNTs studied in this work were produced at the Nuclear Magnetic Resonance Laboratory (FUNDP, Belgium) by catalytic decomposition of acetylene on transition-metal particles (Co, Fe) supported on Al 2 O 3 [17]. They were purified after dissolution of the support in a boiling, concentrated sodium hydroxide aqueous solution and dissolution of the catalysts in concentrated hydrochloric acid aqueous solution.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, engaging the synergistic effects of combined nanotubes and nanoclay in order to reinforce epoxy nanocomposites has been suggested as a way to improve CNT properties. Earlier reports revealed that the addition of clay to CNTs significantly improved the debundling of carbon nanotubes, resulting in fine dispersions in polymer matrix [11][12][13][14][15] Liu et al showed that the addition of clay significantly enhanced the electrical conductivity of single-walled CNT (SWCNT)/epoxy nanocomposites. 11 Similarly, Tang found a significant synergistic effect between clay and multi-walled CNTs (MWCNTs) for reinforcing the chitosan matrix.…”
Section: ⅰ Introductionmentioning
confidence: 99%